COVID‑19 Pandemic and Mental Disorder: Brief Literature Review - Nascimento, Sandra (2020)
The COVID‑19 pandemic has been declared a global health emergency. It is estimated that it may lead to a high level of suffering, and the crisis period is expected to give rise to various challenges in the sphere of mental health, both in the general population and in people with a previous mental disorder. Psychological suffering and generalized anguish due to the immediate impact of the virus on health, but also the need to implement quarantine measures, physical isolation associated with loss in educational and work activities, predict the fear of the disease, the fear of death and uncertainty about the future. On the other hand, it is estimated that the COVID‑19 pandemic may disproportionately affect the most vulnerable populations, namely health professionals and those with a previous history of mental disorder.  Due to the threat of mental health problems that the general population may face and the possible worsening of the underlying condition in patients with previous mental disorders, it is important to assess the various emerging problems. Indeed, mental health services need structural adaptation to deal with the increased risk of psychiatric morbidities, developing and implementing screening and early intervention programs, aimed not only at acute effects but also long‑term or chronic effects of this pandemic.  The preparation of this review article aims to gather, in a rigorous manner, the information dispersed in various scientific sources currently existing on the impact of COVID‑19 infection on mental health, as well as clinical experience in the field. In this way, the authors reviewed the literature, through research through PubMed and Medscape using the keywords “Pandemic”, “COVID‑19”, “Mental Health”, “Mental Disorder”.  The article proposes to develop concisely and summarily some of the particular problems inherent to the pandemic COVID‑19 and mental health, proposing some strategies and interventions to face the situation of crisis experienced. However, the future need for continuous studies and evaluation of the practical experience must be considered, to reorient mental health intervention policies and measures.